Performance of the MeltPro MTB Assays in the Diagnosis of Drug-Resistant Tuberculosis Using Formalin-Fixed, Paraffin-Embedded Tissues. Issue 1 (13th January 2021) - Mu, Jing; Liu, Zichen; Zhang, Chen; Wang, Chongli; Du, Weili; Lin, Haifeng; Li, Kun; Song, Jing; Che, Nanying; Liu, Honggang
Abstract: Objectives: The MeltPro MTB assays for detection of resistance to antituberculosis (TB) drugs perform well in genotypic drug susceptibility testing (DST) of clinical samples, but their effectiveness with formalin-fixed, paraffin-embedded (FFPE) tissues is unknown. Methods: FFPE tissues were obtained from 334 patients with TB. Susceptibility to rifampicin (RIF), isoniazid (INH), and fluoroquinolones was examined using the MeltPro MTB assays, with Xpert MTB/RIF (Xpert) and/or phenotypic DST (pDST) results as references. Samples with discordant results were analyzed by multiplex polymerase chain reaction–targeted amplicon sequencing (MTA-seq). Results: With pDST as the reference, the MeltPro MTB assays sensitivity for RIF, INH, levofloxacin (LVX), and moxifloxacin (MXF) was 95.00%, 96.00%, 100%, and 100%, respectively, and the specificity was 95.15%, 95.92%, 94.69%, and 89.92%, respectively. Concordance was 99.08% between the MeltPro MTB and Xpert (κ = 0.956) for RIF and 95.12% (κ = 0.834), 95.93% (κ = 0.880), 95.12% (κ = 0.744), and 90.24% (κ = 0.367) between the MeltPro MTB and pDST for RIF, INH, LVX, and MXF, respectively. MTA-seq confirmed the discordancy between the MeltPro MTB and pDST for 26 (89.66%) of 29 samples. Conclusions: The MeltPro MTB assays rapidly and efficiently predict Mycobacterium tuberculosis resistance to the main first- and second-line anti-TB drugs in FFPE tissues.